2018
DOI: 10.1177/0093854817749255
|View full text |Cite
|
Sign up to set email alerts
|

Are Supervision Practices Procedurally Fair? Development and Predictive Utility of a Procedural Justice Measure for Use in Community Corrections Settings

Abstract: This study describes the development and refinement of a practical measure for use by community supervision staff to assess the extent to which individuals under community supervision perceive the supervision process as fair. Seven items functioned statistically and theoretically well. Results showed a clear, one-factor structure. The resulting measure demonstrated significant relationships with supervision outcomes of both crime and technical violations across two independent community supervision samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 84 publications
(120 reference statements)
2
33
0
1
Order By: Relevance
“…When we feel that processes are applied in a way that offer us a voice and chance to participate, we perceive our treatment to be more respectful, when decision making is experienced as transparent, consistent and impartial, and we trust in the motives of the authority figure making the decision, we are more likely to perceive our treatment to be procedurally just (Tyler 1990). Research within the CJS, including in policing, prison and probation settings, has tested and supported the relationship between procedural justice and improved outcomes (for example, Beijersbergen et al 2015;Blasko and Taxman 2018;Fitzalan Howard and Wakeling 2019;Gladfelter, Lantz and Ruback 2018;Mazerolle et al 2013). Research on EM, such as that which has been synthesised in this article (and explicitly referenced in some, such as Hucklesby (2009)), supports this being an important feature in how monitored people are treated also.…”
Section: Facilitating Short-term Compliancementioning
confidence: 69%
See 1 more Smart Citation
“…When we feel that processes are applied in a way that offer us a voice and chance to participate, we perceive our treatment to be more respectful, when decision making is experienced as transparent, consistent and impartial, and we trust in the motives of the authority figure making the decision, we are more likely to perceive our treatment to be procedurally just (Tyler 1990). Research within the CJS, including in policing, prison and probation settings, has tested and supported the relationship between procedural justice and improved outcomes (for example, Beijersbergen et al 2015;Blasko and Taxman 2018;Fitzalan Howard and Wakeling 2019;Gladfelter, Lantz and Ruback 2018;Mazerolle et al 2013). Research on EM, such as that which has been synthesised in this article (and explicitly referenced in some, such as Hucklesby (2009)), supports this being an important feature in how monitored people are treated also.…”
Section: Facilitating Short-term Compliancementioning
confidence: 69%
“…Research within the CJS, including in policing, prison and probation settings, has tested and supported the relationship between procedural justice and improved outcomes (for example, Beijersbergen et al . ; Blasko and Taxman ; Fitzalan Howard and Wakeling ; Gladfelter, Lantz and Ruback ; Mazerolle et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research on procedural justice has demonstrated its vital importance in the criminal justice system, leading people to view the law and authority figures as more legitimate, and to greater compliance with, and commitment to obey, rules and law (Lind and Tyler 1988;Tyler 1990) and vice versa. Research in prison and probation settings shows that better justice perceptions are associated with greater compliance with parole conditions, better conduct and psychological well-being in custody and lower reoffending post-release (Beijersbergen et al 2014(Beijersbergen et al , 2015(Beijersbergen et al , 2016Bierie 2013;Blasko and Taxman 2018;Gladfelter, Lantz and Ruback 2018). Perceptions of unfair or unreasonable treatment can lead to resistance to authority and reduced compliance, which is certainly indicated by the study's findings of active defiance and feigned compliance.…”
Section: Discussionmentioning
confidence: 80%
“…Research in prison and probation settings shows that better justice perceptions are associated with greater compliance with parole conditions, better conduct and psychological well‐being in custody and lower reoffending post‐release (Beijersbergen et al . , , ; Bierie ; Blasko and Taxman ; Gladfelter, Lantz and Ruback ). Perceptions of unfair or unreasonable treatment can lead to resistance to authority and reduced compliance, which is certainly indicated by the study's findings of active defiance and feigned compliance.…”
Section: Discussionmentioning
confidence: 97%
“…To test for factor loadings of the items employed in the current study, we subjected all items simultaneously to principal components analysis, with direct oblimin rotation (see Table 2; also, see articles by Baker et al, 2014Baker et al, , 2015Blasko & Taxman, 2018;Hinds & Murphy, 2007;Reisig et al, 2007 that employed a similar factor analytic strategy to test the process-based model). The Bartlett's Test of Sphericity reached statistical significance and the Kaiser-Meyer-Olkin measure of sampling adequacy was .800 (Bartlett, 1954;Kaiser, 1970Kaiser, , 1974.…”
Section: Factor Analysismentioning
confidence: 99%